When does the turning point in China's CO2 emissions occur? Results based on the Green Solow model. (6th February 2015) - Hao, Yu; Wei, Yi-Ming
Abstract: In recent years, the surge in China's CO2 emissions has caused increasing international concern. In this paper, we investigate whether and when the turning point in China's CO2 emissions would occur. A simple yet powerful neoclassical Green Solow model (GSM) is utilized herein as the main forecasting tool. To verify the capability of this framework to address China's economy, a key prediction of the GSM – the convergence in per capita CO2 emissions across Chinese provinces – is empirically verified. By assigning reasonable values to the GSM's key parameters, the trajectories of total CO2 emissions are projected for the three regions of China and the whole country. The forecast results show that, under the benchmark scenario, China's total CO2 emissions would peak around the year 2047. According to the sensitivity analysis, carbon efficiency is the most important determining factor for whether a turning point in total CO2 emissions may occur.